Effect of Tinting on Value Addition of Tuberose (Polianthes tuberosa L.) cv. Prajwal - Kumari, Sweta; Deb, Prahlad (International Journal of Bio-resource and Stress Management, 2018)
Flower craft is one of the most flourish and dynamic enterprises in today’s world. In this craft, value addition and postharvest handling methods of cut flowers is a captivating and trilling craft gaining importance now-a-days. Tuberose (Polianthes tuberosa L.) is a popular cut flower having white coloured fragrant blooms. Tinting or artificial colouring of tuberose may be a potential value addition venture. Tinting is an important value addition technique in flower crops where colour pigments are absent or light or dull. Colouring inflorescences with edible dyes enhance the visual appeal of these flowers, increase their economic value and aesthetic beautification. Studies were carried out Tuberose (Polianthes tuberosa L.) cv. Prajwal to evaluate the ability of flower to obtain and retain different colour shades for the elimination of limited acceptability in market which is mainly due to white colour. Six different food dyes were used as tinting agent in the experiment all in powder form viz, Blue, Apple Green, Tomato red, Orange red, Lemon yellow and Rose pink at a concentration of 1%, 2% and 3% for all. The darkest shades of colours were obtained in 3% concentration while lightest shades in 1%. The maximum vase-life was found in tuberose spikes which were treated with 1% Lemon yellow whereas minimum vase life recorded for Tomato red food dye (3%). The highest Benefit: Cost ratio was obtained for Lemon yellow food dye (1.83) at concentration of 1%. Blue food dye also obtained better net realization (1.69) at 1 % concentration.